PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA SMART BOX DILENGKAPI LKPD QUESTION CARD TERHADAP HASIL BELAJAR SISWA DI SMP PGRI WAINGAPU - Paga Tana, Marlina; Makaborang, Yohana; Rosalia Ndapa Huda, Marleni (Universitas Cokroaminoto Palopo, 2025)
This study aims to examine the impact of the STAD type cooperative learning model using smart box media and equipped with LKPD Question Cards. This investigation was conducted at SMP PGRI Waingapu, with class VIII B functioning as a control group consisting of 24 students, while class VIII C functioning as an experimental group with a total of 23 students in the 2025/2026 academic year. This type of research can be explained through a comparison of the average value of the control group obtained, namely 51.84 (pretest) and 82.27 (posttest), and the average value of the experimental group of 43.07 (pretest) and 73.84 (posttest). The results of hypothesis testing were carried out using a sample t-test which showed an Asmp. Sig (tailed) value of 0.001, which means the value is <0.05 so that H0 is rejected and H1 is accepted. It can be concluded that the STAD type cooperative learning model assisted by smart box media equipped with LKPD Question Cards has a significant effect on the learning outcomes of class VIII C students which is an experimental class at SMP PGRI Waingapu.